Knowledge of pelvic floor muscle exercise (Kegel Exercise) among women at Beserah Polyclinic and Jaya Gading Community Health Clinic - Al-Araji, Laith Issa Yassin; Wan Su, Kamaruzaman (2011)
Kegel exercises can strengthen the muscles around the vagina and increase women’s ability to control and relax these muscles completely. Kegels are often encouraged along with counseling and sex therapy, as a helpful treatment for persistent problems with reaching orgasm. Stress incontinence may develop when urine is released during lifting, sneezing or exercising. Performing Kegel exercises can help many women to relieve these symptoms. Pregnant women will also benefit from Kegel exercises. The objective of this study is to assess the knowledge on Pelvic Floor Muscle Exercise (Kegel Exercise) among women and to identify its association between age, parity, gravidity, educational level, occupational, marital status, and medical problem with urinary incontinence among women in Kuantan. The total number of 200 respondents involved in this study. The data were collected through a self-administered questionnaire, validated the Institutional Review Board of Advocate Healthcare, IRB. Patient ages ranged from 17 to 67 years, and parity ranged from 0 to ≥5. One hundred and twenty six of the 200 women (63%) had heard of Pelvic Floor Muscle Exercise. The independent t-test result showed there is significant in the mean age between ever heard and never heard about PFME group (p < 0.05). Based on the result of chi-square test for demographic factor, which comprises marital status, educational level, occupation, gravidity, and parity. The result showed marital status, occupation, gravidity, and parity has a significant association with knowledge of PFME among women who involved in this research (p < 0.001). Only educational level has no significant association with knowledge of PFME (p > 0.05).